Pengaruh Penerapan Metode Permainan Ranking 1 dalam Pembelajaran IPA terhadap Kemampuan Kerja Sama Siswa Kelas 4 SDN 36 Cakranegara - Syayarathul Khasanah; Muhammad Tahir; Lalu Wira Zain Amrullah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to examine the effect of the Ranking 1 game method in science learning on the cooperative skills of fourth-grade students at SDN 36 Cakranegara. The research employed a pre-experimental design using the one-group pretest–posttest model, in which only a single class was involved without a comparison group. The research sample consisted of 20 fourth-grade students. Data were collected using a questionnaire designed to measure students’ cooperative skills. Prior to hypothesis testing, prerequisite tests including normality and homogeneity tests were conducted. The hypothesis was tested using a t-test to determine the significance of the difference between pretest and posttest results. The results of the hypothesis test indicated that the calculated t-value (11.055) was greater than the t-table value (1.725), leading to the acceptance of the alternative hypothesis and the rejection of the null hypothesis. These findings demonstrate that the Ranking 1 game method has a significant effect on improving students’ cooperative skills in science learning. Therefore, the implementation of game-based learning methods such as Ranking 1 can be considered an effective instructional strategy to enhance student cooperation in elementary science classrooms.